IMPLEMENTATION OF INTERNAL CONTROL IN THE INVENTORY TO DETECTING AND PREVENTING FRAUD IN UMKM LACAFACA BANDUNG CITY - Eldina Alipphia; Andhika Ligar Hardika (SEAN Institute, 2023)
This study aims to find out how fraud can be detected and prevented by using internal control measures in the inventory and storage (warehousing) cycle. The research method used is qualitative research where the results of the qualitative study have a meaningful unique understanding. Data collection techniques were carried out using triangulation (a combination of observation, interviews, documentation). Data analysis is qualitative or inductive. Then the place used in the initial research was the Lacafaca UMKM. The results showed that internal control was not effective in preventing and detecting fraud in the inventory and warehousing cycle at UMKM Lacafaca. If the risk of fraud cannot be handled and prevented adequately, this risk can harm the company. The application of written ethical standards to companies can be a solution to prevent fraud in Lacafaca SMEs